Scorpion sting cases in children of coastal region of Balochistan: a case report - Tahira Zubair; Saeed Ahmad Khan; Javeria Amjad (Journal of the Pakistan Medical Association, 2025)
Scorpion bites are a great health concern in various regions of the world, including the coastal areas of Balochistan. Mortality is especially high in the paediatric population. This case report describes the presenting symptoms, management, and fate of two children who presented with scorpion bite from the coastal regions of Balochistan. The purpose of this report is to highlight these serious issues, occurring in this particular area, and the challenges faced by healthcare professionals in the management of such cases. The use of Doxazosin as physiological antidote of scorpion venom, due to non-availability of the conventional drug (Prazosin) in one of our patients, proved to have favourable outcome and comparable efficacy. Keywords: Scorpion bites, Balochistan, Paediatric, Symptoms.